Understanding of Machinery Technology in Understanding Renewable Energy Towards Indonesia Go Green - Fathan Mubina Dewadi; Amir; Rizki Aulia Nanda; Karyadi; Cahyo Wibowo (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
There are 10 countries with the least pollutant levels in the world. This is what triggers the example of other countries. So it is necessary to explore what makes these countries superiors in environmental issues so that they are ranked in the top 10 on the world scales according to the U-Earth Team. However, a clean country can be due to a small area or a small population so that the pollutants become small. The method used for this research is a literature study with a qualitative research type based on what already exists. What is meant here is the research method with reference to the existing literature. The stages of this research are looking for problems, then collecting the existing literature. Then after that, examine the related parameters related to the problem. The final step are to find a solution to the existing problem. The importance of progress of going green in this great country so that it can save much human beings. You could say, in terms of SO2, NOx and Dust emission levels in Indonesia, Indonesia has a fairly high ratio, so it is important to check CO2 in every vehicle and industry as well as limit personal use. The essence of this research is that public education about go green energy and minimizing pollution is very much needed.